Inflammatory Bowel Disease: An Emergent Disease Among Ethiopian Jews Migrating to Israel. Issue 3 (March 2015) - Bar-Gil Shitrit, Ariella; Koslowsky, Benjamin; Kori, Michal; Paz, Kalman; Adar, Tomer; Israeli, Eran; Ben-Horin, Shomron; Berdichevski, Tania; Coscas, Daniel; Gal, Eyal; Odes, Shmuel; Shaul, Ron; et al.
Abstract : Background: The development and characteristics of inflammatory bowel disease (IBD) in Ethiopian Jewish immigrants to Israel were investigated. Methods: A case-control study was conducted in 7 tertiary care hospitals in Israel. Patients of Ethiopian origin with IBD >6 months were included. Time of disease onset after immigration and age at diagnosis were recorded. Randomly chosen patients with IBD of Ashkenazi Jewish origin served as controls. Demographics and clinical parameters were compared between the 2 cohorts. Results: Thirty-two Ethiopian patients with IBD were compared with 33 Ashkenazi Jewish patients with IBD. Crohn's disease (CD) was more prevalent than ulcerative colitis (UC) in the Ethiopian group compared with the Ashkenazi group (94% versus 73%, P = 0.02). No Ethiopian-origin patient had a positive family history of IBD compared with 42% of Ashkenazi-origin patients ( P < 0.001). Arthritis was more common in Ashkenazi than in Ethiopian patients (27% versus 3%, P < 0.01). One Ashkenazi patient with CD had upper gastrointestinal involvement compared with 7 (23%) in the Ethiopian group ( P < 0.02). All other clinical measures were similar between the 2 cohorts. The Ethiopian group lived in Israel with a mean of 13 ± 5 years, and 75% were born in Ethiopia. The shortest time between immigration and developing IBD was 8 years (range, 8–26; median 16 yrs). No Ethiopian patient was diagnosed before immigration. Conclusions: Ethiopian Jews migrating to Israel are at risk of developing IBD. Larger cohorts are needed to determine the relative importance of environmental and genetic factors that cause IBD in these patients. Abstract : Article first published online 8 January 2015.